THE ROLE OF INVESTMENTS IN ENHANCEMENT OF ENERGY EFFICIENCY - Khusanov Fakhriddin (Journals Park Publishing, 2024)
Investing in energy efficiency will have a positive impact on reducing future energy demand and improving the quality of services. Therefore, conducting scientific research in the direction of ensuring energy saving in the economy and improving energy efficiency is of great practical importance.
Keywords: Investment, energy efficiency, renewable energy, energy supply.